PERAN PEMERINTAH TERHADAP PENGEMBANGAN POTENSI EKONOMI KREATIF DAN PARIWISATA DI KABUPATEN HULU SUNGAI UTARA - Hartiningsih (Jurnal Kebijakan Pembangunan, 2019)
Hulu Sungai Utara is a regency that produces a lot of handicrafts from plaited, embroidered, carved wood and so on. Crafting is one of 16 sub-sectors of the creative economy. The development of creative economy form of crafts such as rattan, purun, water hyacinth and so on has been running for decades. Unfortunately the crafting sector has not been much in touch with innovation. Likewise, the tourism sector is still lacking attractive tourism destinations, except Candi Agung. This research was conducted to provide an overview of the role of government in the development of creative economy and tourism, and analyse the potential and obstacles faced by Hulu Sungai Utara Regency. The method use is a descriptive qualitative. The results of the study illustrate that the development of creative economy and tourism in the Hulu Sungai Utara regency is not yet significant, while in general the government is quite instrumental in the development of the creative economy and tourism by providing training, coaching, facilitating loans to banks, and various other development, developing legal aspects for Pokdarwis on the tourism sector. Although, greater attention is still needed, especially in terms of increased budgeting, in order to accelerate the development of tourist destinations that have a potential attraction. The general obstacle to both creative economy and tourism lies in the lack of funds, specific constraints, in the organizational structure there is no creative economy specific agency. Most creative economy do not yet have high sales value and market share is still largely at local scale. As for tourism, aside from limited funds, it is also being developed: the local government has not yet made tourism a priority sector. It is recommended, because the two sectors have the potential to drive the community's economy and the regional economy, as well as the potential to alleviate unemployment, the agencies that manage these sectors can work together and collaborate intensively with one another to develop their potential. Abstrak Kabupaten Hulu Sungai Utara termasuk kabupaten yang banyak memproduksi Kriya dari anyaman, sulaman, kayu ukir dan sebagainya. Kriya merupakan salah satu dari 16 sub sektor ekonomi kreatif (ekraf). Perkembangan ekraf berupa kriya seperti rotan, purun, enceng dan sebagainya sudah berjalan puluhan tahun. Sayangnya kriya tersebut belum banyak sentuhan inovasi. Demikian pula sektor pariwisata masih minim destinasi wisata menarik, kecuali Candi Agung. Penelitian ini dilakukan untuk memberikan gambaran mengenai peran pemerintah terhdap pengembangan potensi ekraf dalam mendukung sektor pariwisata dan kendala yang dihadapi oleh Kabupaten Hulu Sungai Utara. Penelitian ini merupakan penelitian deskriptif kualitatif, pengumpulan data dilakukan melalui wawancara mendalam dan observasi lapangan. Data kemudian dianalisis secara deskriptif. Hasi penelitian menunjukkan bahwa perkembangan ekraf maupun pariwisata di Kabupaten Hulu Sungai Utara belum begitu signifikan. Pemerintah Kab. HSU sudah cukup berperan terhadap pengembangan ekonomi kreatif maupun pariwisata dengan memberikan berbagai pelatihan dan pembinaan bagi pelaku ekonomi kreatif dan juru kunci wisata religi, hingga menerbitkan SK bagi Pokdarwis. Dengan demikian, masih diperlukan perhatian lebih besar lagi dari Pemerintah Daerah terutama segi peningkatan penganggaran. Kendala umum yang ada dalam pengembangan ekraf dan pariwisata adalah keterbatasan dana. Kendala khusus dalam pengembangan ekraf adalah tidak ada bidang ekraf dalam struktur organisasi. Kendala di sektor pariwisata adalah keterbatasan dana dan belum menjadi program prioritas Pemerintah Daerah, selain itu belum ada sinergi antar instansi terkait. Rekomendasi penelitian ini adalah karea sektor ekraf dan pariwisata berpotensi sebagai penggerak ekonomi masyarakat dan ekonomi daerah, maka antar dinas berkomitmen untuk saling bersinergi untuk mengembangan ekraf dan potensi destinasi wisata yang dimiliki. Role, Goverenment,Development,CreativeEconomy,Tourism